Effect of cultivar, fulvic acid and the interaction between their on some physical and chemical properties and yield of broccoli Brassica oleracea var. Italica) - Batoul Hanoon Faleh Al-Zubaidi; Walid Allawi Abbawi (University of Thi-Qar Journal of agricultural research, 2022)
The field experiment was conducted during the fall agricultural season 2021-2022 in the Department of Horticulture and Gardens, Al-Kut municipality; the experiment was completed on 15 February. 2022, to study the effect of the cultivar, fulvic acid, and their interaction on some broccoli's physical and chemical properties. The study included two factors: cultivars, MATSURI, DOMO, JASSMINE, and the second factor has four concentrations of fulvic acid, which are: (0, 1, 2, 3) ml l-1. The experiment included twelve treatments and three replications, so the total experimental units became (36). A factorial experiment was applied with a split-block system within the Randomized Complete Block Design (R.C.B.D), and the results were statistically analyzed using the statistical program (GenStat). The results were compared using the LSD test at a probability level of 0.05. While the JASSMINE cultivar was superior in the wet weight of the main disc, the dry weight of the main disc, the diameter of the main disc and the weight of the side disc if the values ​​were (851.7 gm tablet-1,93.42 gm tablet-1,21.33 cm,147.25 gm tablet-1),respectively, and the MATSURI hybrid was superior in The number of side tablets reached (5.00 plant-1 tablets). The plants treated with a concentration of (3) ml L-1 of fulvic acid excelled in the content and wet weight of the main disc, dry weight of the main disc, the diameter of the main disc, the number of side discs, and the weight of the side disc Where the values ​​were (856.3 gm Tablet-1, 100.44 gm Tablet-1, 21.33 cm, 147.56 gm Tablet-1, 5.56 gm Tablet-1) respectively. The dual interaction between the cultivar and fulvic acid concentrations had a significant effect, as the interaction treatment between the cultivar JASSMINE and the concentration of fulvic acid (3) ml L-1 in the wet weight of the main disc, the dry weight of the main disc and the weight of the side disc were (990.7 gm disc-1, 124.00) gm tablet-1, 182.33 gm tablet-1)respectively.Keywords: fulvic acid; Brassica oleracea var; broccoli